Nano‐Sized AlPO4 Coating Layer on Graphite Powder to Improve the Electrochemical Properties of High‐Voltage Graphite/LiNi0.5Mn1.5O4 Li‐Ion Cells. Issue 9 (26th June 2019) - Zeng, Huanna; He, Jia; Fang, Danyang; Liang, Yaohui; Zhao, Ruirui; Cai, Yuepeng; Lu, Dongsheng
Abstract : A high‐voltage graphite/LiNi0.5 Mn1.5 O4 (LNMO) system is a promising candidate for next‐generation Li‐ion batteries with a high energy density. However, it has the drawback of severe capacity fading caused by the consumption of active Li + ions due to the reduction of the products of electrolyte oxidation and LNMO dissolution from the LNMO cathode on the graphite anode. Herein, graphite coated with different amounts of AlPO4 (0.5, 1, and 2.5 wt%) is prepared by an electrostatic attraction combined with a precipitation conversion method, and used as an anode for the LNMO/graphite full cell. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and elemental mapping images show that AlPO4 disperses homogeneously on the surface of graphite, and its thickness is between 10 and 30 nm. Electrochemical measurement results show that LNMO/AlPO4 @graphite cells show better cycling stability and higher coulombic efficiency than the LNMO/graphite cell. Among them, the LNMO/0.5 wt% AlPO4 @graphite cell shows the best cycling stability. By combining all the analytical results, the improvement mechanism of LNMO/AlPO4 @graphite cells is mainly that the side reactions that consume the active Li + ions are greatly reduced because the AlPO4 coating can block the migration of the products of electrolyte oxidation and LNMO dissolution to the graphite. Abstract : Graphite coated with nano‐sized AlPO4 is prepared by an electrostatic attraction combined with a precipitation conversion method. The modified graphite/LiNi0.5 Mn1.5 O4 (LNMO) cell exhibits an enhanced cycling stability, because the AlPO4 coating can block the migration of the products of electrolyte oxidation and LNMO dissolution to the graphite, thus reducing the consumption of active Li + ions.